2019
DOI: 10.1016/j.ejmech.2019.111667
|View full text |Cite
|
Sign up to set email alerts
|

Sulfide, sulfoxide and sulfone bridged acyclic nucleoside phosphonates as inhibitors of the Plasmodium falciparum and human 6-oxopurine phosphoribosyltransferases: Synthesis and evaluation

Abstract: sulfoxide and sulfone bridged acyclic nucleoside phosphonates as inhibitors of the Plasmodium falciparum and human 6-oxopurine phosphoribosyltransferases: Synthesis and evaluation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The thia-linked nucleotide analogs (thia-ANPs, Scheme 1 ) were prepared analogously to a known procedure 31 . Mitsunobu reaction of adenine with alcohols 1a and 1b in hot dioxane afforded compounds 2a and 2b , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The thia-linked nucleotide analogs (thia-ANPs, Scheme 1 ) were prepared analogously to a known procedure 31 . Mitsunobu reaction of adenine with alcohols 1a and 1b in hot dioxane afforded compounds 2a and 2b , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The heteroatom increases the flexibility of the chain and modulates its position in the active site (compare activity of 3a and 3b ). While sulfur enables a change in the geometry via oxidation 31 , but results in the loss of the inhibitory activity (compare 3a and 4a ), nitrogen makes a facile attachment of the side chain possible. Moreover, these aza-ANPs are prochiral inhibitors ( 9a–9g and 17) , since nitrogen atom is protonated at physiological conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compounds bearing a phosphonate moiety in their N9 side chain are well known as antiviral agents, such as adefovir, tenofovir, and cidofovir [7]. Lately, it was found that ANPs possess inhibitory activity against hypoxanthine-guanine-xanthine phosphoribosyltransferase of the parasite Plasmodium falciparum, and several research groups are focused on the development of this topic [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%